Efficacy of 0.05% epinastine and 0.1% olopatadine for allergic conjunctivitis as seasonal and preseasonal treatment - Mizoguchi, Takanori (Clin Ophthalmol, 2017)
PURPOSE: To evaluate the efficacy and safety of 0.05% epinastine and 0.1% olopatadine eye drop preparations as seasonal and preseasonal treatments in patients with seasonal allergic conjunctivitis (SAC). SUBJECTS AND METHODS: This was a prospective, randomized, case-control study involving two institutions. The subjects were patients diagnosed with SAC at two institutions between February and March in 2014. To examine the clinical effects of seasonal treatment, 0.05% epinastine and 0.1% olopatadine were administered, and their effects were investigated every 2 weeks (Stage 1). To evaluate the clinical effects of preseasonal therapy, in January 2015, the same eye drop preparations as adopted in Stage 1 were administered to patients who had participated in Stage 1 and provided consent to participate in this study, and their effects were investigated every month (Stage 2). RESULTS: In Stage 1, the 0.05% epinastine group consisted of 43 patients, and the 0.1% olopatadine group consisted of 42 patients. There were significant improvements in the total symptom and objective finding scores at each time point after administration in comparison with those before its baseline, but there were no significant differences between the two groups. In Stage 2, the 0.05% epinastine group consisted of 15 patients, and the 0.1% olopatadine group consisted of 14 patients. The rate of change in the total symptom score in comparison with that at the baseline of preseasonal treatment was significantly higher in the 0.1% olopatadine group 1 month after the start of treatment, suggesting symptom deterioration (P=0.025). There was no significant difference in the rate of change in the total objective finding score between the two groups. CONCLUSION: Seasonal treatment with 0.05% epinastine or 0.1% olopatadine was equally effective for patients with allergic conjunctivitis. However, for preseasonal therapy, 0.05% epinastine was more effective than 0.1% olopatadine.